Perkembangan Tarekat Dalam Lintasan Sejarah Islam Di Indonesia - S, Muh Nasir (Jurnal Adabiyah, 2011)
In Islam, tariqat is known as a ritual institution. It aims at getting nearer to Allah. The sufi orders believe that Thariqat was from Prophet Muhammad saw. In its progress, tariqat was then organized by a Syekh who teaches all his disciplines. In Indonesa, tariqat is devided generally into two categories, that is the mu’tabar tariqat and local tarikat. All tariqat considered mu’tabarah came from outside to Indonesia before the Independent day of Indonesia.